2022
DOI: 10.1371/journal.pone.0275669
|View full text |Cite
|
Sign up to set email alerts
|

Commitment to protective measures during the COVID-19 pandemic in Syria: A nationwide cross-sectional study

Abstract: Background Severe acute respiratory syndrome coronavirus 2 continues to impose itself on all populations of the world. Given the slow pace of vaccination in the developing world and the absence of effective treatments, adherence to precautionary infection control measures remains the best way to prevent the COVID-19 pandemic from spiraling out of control. In this study, we aim to evaluate the extent to which the Syrian population adheres to these measures and analyze the relationship between demographic variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Komitmen pencegahan adalah afeksi sebagai manifestasi dari kesadaran untuk melakukan atau bertindak (Merritt, 2011;Shibani et al, 2022), yang mengarah pada upaya pencegahan menularnya COVID-19. Skala terdiri dari 2 item yaitu "Saya merasa bahwa mengikuti aturan yang terkait upaya pencegahan penyakit menular itu diperlukan" dan "Saya merasa penting memiliki komitmen pencegahan".…”
Section: Variabel Penelitian Dan Pengukurannyaunclassified
“…Komitmen pencegahan adalah afeksi sebagai manifestasi dari kesadaran untuk melakukan atau bertindak (Merritt, 2011;Shibani et al, 2022), yang mengarah pada upaya pencegahan menularnya COVID-19. Skala terdiri dari 2 item yaitu "Saya merasa bahwa mengikuti aturan yang terkait upaya pencegahan penyakit menular itu diperlukan" dan "Saya merasa penting memiliki komitmen pencegahan".…”
Section: Variabel Penelitian Dan Pengukurannyaunclassified
“…One pathway originates from an individual perspective, according to the health belief model, which posits that individual emotion and risk perception affect health-related behaviors ( Rosenstock, 1974 , 1977 ; Weinstein and Nicolich, 1993 ). Many studies supported the individual emotional and cognitive approach in explaining anti-pandemic behaviors ( Kowalski and Black, 2021 ; Shiloh et al, 2021 ; Shibani et al, 2022 ; Anderson and Hobolt, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although pandemic prevention experts referred to people over the age of 65 and/or with comorbidities as vulnerable groups during the pandemic, other groups may also be vulnerable due to unmet needs and other difficulties, such as homelessness ( Bodenmann et al, 2020 ). Some studies have found that compared to their counterparts, people of younger age, lower income, lower educational level, or without a full-time job were less compliant with anti-pandemic behaviors ( Armitage et al, 2021 ; Kowalski and Black, 2021 ; Kanazawa, 2022 ; Shibani et al, 2022 ). According to our previous hypothesis H1, this may be because their normal life was disrupted more, and their needs were more dissatisfied than those of their counterparts.…”
Section: Introductionmentioning
confidence: 99%